Characterisation and detection of dasheen mosaic potyvirus in Zantedeschia : a thesis presented in partial fulfilment of the requirements for the degree of Master of Horticultural Science in Plant Health at Massey University, Palmerston North, New Zealand - Matthews, Christine Grace (Massey University, 1995)
Four potyvirus isolates believed to be dasheen mosaic potyvirus, the most frequently occurring virus to infect members of the Araceae, were obtained from Caladium, Colocasia, Xanthosoma and Zantedeschia in world-wide locations. Properties of these isolates such as particle length, serological relatedness, electrophoretic mobility of coat proteins and genomic characteristics were compared. Serologically distinct strains of dasheen mosaic potyvirus were apparent amongst the isolates. The difference in the serological relationship was coupled with a variation in symptom expression. An isolate from Colocasia esculenta (L.) Schott was not serologically related to the other isolates. Further isolates from C. esculenta also exhibited no relationship. The modal length was different as well as the ability of complementary deoxyribonucleic acid, produced to the viral ribonucleic acid, to bind with some of the primers used in the polymerase chain reaction. This evidence led to the proposal that the isolate from C. esculenta was not dasheen mosaic potyvirus; this virus is tentatively named taro feathery mottle potyvirus. Cytoplasmic inclusion protein aggregates of dasheen mosaic potyvirus were purified from infected leaf tissue. SDS-polyacrylamide gel electrophoretic analysis of samples revealed a major band with an estimated molecular weight of 68,000 daltons. Such a band was absent from healthy tissue samples. The ATPase activity in samples from each purification step was determined by measuring the amount of [32P] released from the [λ-32P]ATP during incubation with the cytoplasmic inclusion protein. The level of ATPase activity in each sample showed a strong correlation with the amount of protein that was present. In a limited survey of commercial plantings twenty nine tubers grown for cutflower or tuber export were obtained from seven properties at different locations in New Zealand and grown on in a greenhouse. Each plant was indexed for virus infection. Electron microscopy revealed that plants from three of the properties contained 720nm flexuous rods. Samples from all but two plants tested positive to a potyvirus group antiserum using the enzyme-linked immunosorbent assay. The remaining two plants tested positive in microprecipitin and rapid immune electron microscopy tests to an antiserum prepared to a member of the carlavirus group. Particles from these plants were mechanically transmitted to Nicotiana tabacum 'Havana'. Rod-shaped particles of 300nm were observed in plants from four properties and tested positive to tobacco mosaic tobamovirus antiserum using a microprecipitin test. While inoculations to herbaceous indicators resulted in no symptoms, 300nm particles were observed in samples from the indicator plants. Tomato spotted wilt tospovirus, potato X potexvirus and cucumber mosaic cucumovirus, reported to infect Zantedeschia spp, were not detected.
Keywords: Calla lilies -- Diseases and pests; Mosaic diseases; Plant viruses